2008
DOI: 10.2139/ssrn.1263272
|View full text |Cite
|
Sign up to set email alerts
|

Real Time Forecasts of Inflation: The Role of Financial Variables

Abstract: The working paper series promotes the dissemination of economic research produced in the Department of the Treasury (DT) of the Italian Ministry of Economy and Finance (MEF) or presented by external economists on the occasion of seminars organised by MEF on topics of institutional interest to the DT, with the aim of stimulating comments and suggestions. The views expressed in the working papers are those of the authors and do not necessarily reflect those of the MEF and the DT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…This allows us to fully exploit the co-movement in our dataset, without losing any information. Moreover, in contrast to MIDAS models, like the one proposed in Monteforte and Moretti (2010), the proposed framework does not require to impose high frequency data as predetermined variables. It therefore allows to disentangle model-based "news" from each release and then to assess their impact on forecast revisions.…”
Section: Tracking Forecast Revisions: March 2009mentioning
confidence: 99%
“…This allows us to fully exploit the co-movement in our dataset, without losing any information. Moreover, in contrast to MIDAS models, like the one proposed in Monteforte and Moretti (2010), the proposed framework does not require to impose high frequency data as predetermined variables. It therefore allows to disentangle model-based "news" from each release and then to assess their impact on forecast revisions.…”
Section: Tracking Forecast Revisions: March 2009mentioning
confidence: 99%
“…Modugno (2013) and Monteforte and Moretti (2013) both nowcast year-over-year inflation rates rather than monthly inflation rates. Using the same underlying monthly models and the same cases described above, Table 5 assesses the ability of the models to nowcast yearover-year inflation.…”
Section: Nowcasting Year-over-year Inflationmentioning
confidence: 99%
“…In one exception, Modugno (2013) applies a dynamic factor model-with a larger number of monthly, weekly, and daily data series compared with the limited set of variables we work with-to nowcast year-over-year U.S. CPI inflation. Monteforte and Moretti (2013) use a combination of a dynamic factor model to construct a measure of core inflation and mixed frequency data in the context of a mixed data sampling (MIDAS) regression model based on Ghysels et al (2004Ghysels et al ( , 2005 to nowcast year-overyear euro area inflation. We present results for nowcasting U.S. monthly, year-over-year, and quarterly inflation, especially because the latter is the usual jumping-off point for economists doing quarterly forecasting exercises.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Marcellino and Schumacher (2010) and more recently Ferrara and Marsilli (2014) showed that combining factorial analysis with MIDAS approach (into the so-called factor-augmented MIDAS model) successes in addressing large databases with mixing frequencies. Monteforte and Moretti (2013) showed that including daily variables using the MIDAS framework helps to improve inflation forecasts with respect to models that only consider monthly variables in the euro area.…”
mentioning
confidence: 99%